A statistical comparative study between the functions of alcohols and thiols using quantum chemistry methods - Tudoran Marina Alexandra (Proceedings of the International Symposium on Analytical and Environmental Problems, 2022)
Using the QSAR method, the present work aims to comparatively study the relationship between solubility (data from literature) and several physical and chemical parameters (computationally calculated) for two classes of analogue compounds, i.e. alcohols and their corresponding thiols. The obtained results show that there are significant differences between the ways in which solubility can be computationally determined for these two classes.